DETERMINAN TINGKAT PENGANGGURAN TERBUKA (TPT) KABUPATEN/KOTA DI PROVINSI BALI - Miranda Hotmauli Sinambela; I Wayan Wenagama (E-Jurnal Ekonomi Pembangunan, 2023)
The purpose of this study was to determine the simultaneous and partial effects of number of tourist, investment, dan average length of schooling on the open unemployment rate in the Bali Province regencies/cities. This research was conducted in nine regencies/cities in Bali Province. The data used is secondary data obtained from the Bali Province Central Bureau of Statistics and Bali Province Department of Tourism from 2017-2021. The number of samples in this study was 45. Data collection was carried through non-participant observation. The analysis technique used is panel data regression. Based on the result of the study it was found that the number of tourist, investment, and average length of schooling have a simultaneous effect on the open unemployment rate. The number of tourist has a negative and significant effect on open unemployment rate. Investment has a positive and insignificant effect on open unemployment rate. The average length of schooling has a positive and significant effect on open unemployment rate.